THE IMPLEMENTATION OF SIMULATION TECHNIQUE ASSISTED WITH REALIA IN SPEAKING CLASS - Dewa Ayu Ari Wiryadi Joni (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2020)
The present study aimed at improving speaking skill through simulation technique assisted with realia toward the first semester students of ELESP FKIP Unmas Denpasar in academic year 2019/2020. The subjects consisted of 32 subjects. Based on the result of the pre-test which was carried out in pre-cycle, the subjects’ speaking skill in performing the oral dialogue was categorized to be insufficient. This present study was then carried out through implementing simulation technique assisted with realia in two-planned cycles and in each cycle consisted of two successive sessions. The results of post-tests in each cycle showed that there was a significant improvement concerning the subjects’ speaking skill in which it improved from insufficient to good level. This research also showed that there were positive responses concerning the technique implemented in improving the subjects’ speaking skill. To sum up, the present study provided empirical evidences that speaking skill of the first semester students of ELESP FKIP Unmas Denpasar in academic year 2019/2020 could be improved through simulation technique assisted with realia.